The Effect Of CAR, NPL & LDR On The Profit Improvement Of Regional Development Bank In Indonesia By Using Credit Growth As Intervening Variable (Research on Regional Development Banks in Java, Bali & NTT) Period 2011 – 2015 - Ririn Poerwanti; Titis Puspitaningrum Dewi Kartika (IJEBD (International Journal of Entrepreneurship and Business Development), 2018)
Purpose: This study aimed to analyze the effect of CAR, NPL, and LDR on credit growth in the 8 (eight) Regional Development Bank in Indonesia, especially in Java, Bali & NTT in the period 2011-2015. Design/methodology/approach: The samples used were taken using census method which includes the entire population.. Findings: Partial test result indicate that CAR is negative and significant effect on credit growth as well as a significantly positive effect on earning growth. NPL ratio partially no significant effect on credit growth but significant effect on earning growth. Research limitations/implications: LDR no significant effect on credit growth but significantly and positively affect profit growth while existing credit growth is able to mediate the perpetually perfect (perfect mediation) between CAR, NPL and LDR on regional development bank profit growth in Java, Bali and NTT in the period 2011 to 2015. Practical implications: 2. The financial ratios assessed from the CAR, NPL and LDR before involving intervening variables of credit growth significantly affected the increase in profit at Regional Development Banks in Java, Bali and NTT as evidenced by simultaneous test results with P-value of F or significance of 0.019 <a '(5%). Originality/value: The ratio of CAR, NPL and LDR significantly affects credit growth in Regional Development Banks in Java, Bali and NTT through simultaneous testing with P value of F or a significance level of 0.004 <a '(5%). Paper type: Research paper